Different measures of economic growth lead to different conclusions? - Urban Gråsjö; Tobias Arvemo (European Regional Science Association (ERSA), 2010)
Economic growth is defined as the percentage output increase in an economy, e.g. a nation, a region or a municipality. The economic growth is closely related to the industrial structure, health, demography and income distribution of the economy. The most used measure for national economic growth is the change in Gross Domestic Product (GDP). GDP measures the value added of all goods and services produced in the economy. The production of goods and services generates primary incomes for households and another method of measuring GDP is therefore to add up all incomes. One part of this income consists of the sum of all wages paid to households. When regional growth studies are conducted, a common measure of economic growth is the wage sum. One reason for this may be the limited access to GDP data on regional level. However, in Sweden there exists GDP data on municipal level, which enables studies where the effects of using GDP data or wage data can be compared. The aim of the present study is to investigate the difference the use of the measures GMP (Gross Municipal Growth) and the sum of wages has on growth models. Since the two measures are similar but not identical the choice of measure of growth can influence the conclusions of an investigation. This might lead to contradictory results on for instance how the access to university research influences the economical growth (Andersson, Gråsjö & Karlsson 2007, 2008). Preliminary results indicate high positive correlations between changes in GMP and wage sum on municipal level. However, when data on GMP per capita and wage sum per capita are used, the correlations are still positive but much smaller. References Andersson M., Gråsjö U. & Karlsson C. (2007), Regional Growth and Accessibility to Knowledge Resources: A Study of Swedish Municipalities, The ICFAI Journal of Knowledge Management, July 07 Andersson M., Gråsjö U. & Karlsson C., (2008), Human Capital and Productivity in a Spatial Economic System, Annals of Economics and Statistics, No 87/88 - 2008.
Keywords: 330